2018
DOI: 10.1128/aem.00967-18
|View full text |Cite
|
Sign up to set email alerts
|

A High-Resolution Time Series Reveals Distinct Seasonal Patterns of Planktonic Fungi at a Temperate Coastal Ocean Site (Beaufort, North Carolina, USA)

Abstract: There is a growing awareness of the ecological and biogeochemical importance of fungi in coastal marine systems. While highly diverse fungi have been discovered in these marine systems, still, little is known about their seasonality and associated drivers in coastal waters. Here, we examined fungal communities over 3 years of weekly sampling at a dynamic, temperate coastal site (Pivers Island Coastal Observatory [PICO], Beaufort, NC, USA). Fungal 18S rRNA gene abundance, operational taxonomic unit (OTU) richne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
50
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(63 citation statements)
references
References 74 publications
11
50
2
Order By: Relevance
“…4A) includes samples from Stations A to C when the water temperature is <19 C, relative to the warmer offshore temperatures >22 C at Stations D and E in these same transects. This temperature-related seasonal signal aligns with previous studies at Station A, which found that temperature is the strongest environmental factor correlated with microbial community changes (Ward et al, 2017;Duan et al, 2018) as well as other studies that observed secondary seasonal patterns layered on top of strong spatial patterns (Fortunato et al, 2012). Supporting this hypothesis, taxa that increased in these cool winter samples were previously identified as winterassociated in the PICO time series (Ward et al, 2017).…”
Section: Spatial Patterns In Microbial Communities Across Coastal Trasupporting
confidence: 90%
See 2 more Smart Citations
“…4A) includes samples from Stations A to C when the water temperature is <19 C, relative to the warmer offshore temperatures >22 C at Stations D and E in these same transects. This temperature-related seasonal signal aligns with previous studies at Station A, which found that temperature is the strongest environmental factor correlated with microbial community changes (Ward et al, 2017;Duan et al, 2018) as well as other studies that observed secondary seasonal patterns layered on top of strong spatial patterns (Fortunato et al, 2012). Supporting this hypothesis, taxa that increased in these cool winter samples were previously identified as winterassociated in the PICO time series (Ward et al, 2017).…”
Section: Spatial Patterns In Microbial Communities Across Coastal Trasupporting
confidence: 90%
“…This study builds on previous research that found strong temperature‐associated annual patterns in microbial communities at the PICO time series (Ward et al ., ; Duan et al ., ). These PICO‐LOVE transects begin at the PICO time series site (Station A) and cross the mid‐Atlantic continental shelf, depth < 160 m (Day et al ., ), for a total distance of 87 km to Station E, at the edge of both the continental shelf break and the warm, oligotrophic waters of the Sargasso Sea.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Other marine debris such as wood also harbour fungi, suggesting that Fungi are well adapted to live on different types of floating marine substrates (Kettner, Oberbeckmann, Labrenz, & Grossart, 2019; Kettner et al., 2017). The abundance and diversity of fungi in coastal waters varies seasonally in response to environmental variables such as particulate organic carbon (Duan et al., 2018; Taylor & Cunliffe, 2016), which could also affect how and which fungal taxa colonize plastics.…”
Section: Introductionmentioning
confidence: 99%
“…Marine microbial plankton, including fungi, are exposed to a highly fluctuating environment, which is reflected in changing diversity and structure (Gilbert et al, 2012;Lucas et al, 2016;Taylor and Cunliffe, 2016;Teeling et al, 2016;Duan et al, 2018). The dynamics within marine microbial communities can be described by different patterns (Needham et al, 2013), ranging from relatively small variations around an average to rapid increases and decreases within a very short time.…”
Section: Introductionmentioning
confidence: 99%